The Utilization of Avocado Seed Powder (Persea americana Mill) as a Metal Adsorbent of Cu(II) - Juliyanto, Juliyanto; Abram, Paulus H. (Universitas Tadulako, 2023)
Avocado is a fruit that has a high nutritional value are beneficial for human health. In the fruit of the avocado are seeds of avocado that are still less utilization thus discarded and become waste. The content in avocado seeds can be used as an adsorbent. This research utilizes avocado seed powder (Persea americana Mill). As Metal Cu(II) Adsorbent. This study aims to determine the water content, ash content, and optimum pH of the adsorption of Cu(II) metal using avocado seed powder. Determining the concentration of Metal Cu(II) using the tool spectrophotometry Atomic Absorption (AAS). Determination of the optimum pH is done by varying the pH 2, pH 3, and pH 4. This research results show that the water content is 4.88% and the ash content is 1.94%. The results of the analysis of the optimum pH to adsorb Cu(II) metal is pH 4 with a percentage of metal that is absorbed by 65.515%. Based on the results of the study showed that avocado seeds can be used as adsorbents.